지방의회의 지방정부 재정감시 강화방안 - 박근후; 강장석 (의정논총, 12(1), 2017)
지방재정의 건전성 확보를 위해서는 중앙정부차원의 통제도 필요하지만 지방자치단체의 자체적인 통제가 중요하다. 이 연구는 지방의회의 지방재정감시방안을 모색하고 있다. The unsound fiscal condition of local government lead to undermine local government’s inherent role(sustain democracy, supply service or goods) and result in external diseconomies and financial spillovers. It could shift financial burdens to next generation and bring about generational conflict. And it also impute debt to the residents of future who don’t reside now. So, local government must be responsible for keeping their own fiscal soundness and need effective control system. The control mechanism over the local finance are control by the central government and local council. In this article, I suggest the measures to strengthen local council’s financial control in Korea. The suggestions of this report to strengthen local council’s financial control are as follows. Establishing the principle of no budget expenditure without law(ordinance). Securing the autonomy of human resources affairs(to decide the number of staffs who work in local council, personnel appointments and so on). Extending the committee members’serving term for one committee to have specialty and deliberate the budget. Making rules for pre budget consideration of local council, Making system for local council to state suggestion to the budget guideline and mid-term fiscal plan Running ‘committee on budget and accounts’ as standing committee. Changing the budget consideration process from bottom-up budgeting to top-down and the committee on budget and accounts’ review the budget proposal at the macro level first and standing committee deliberate the budget proposal at the micro level secondly. Advancing time for metropolitan council to audit and inspection. Making system for local council to examining the accounts independently. KCI Citation Count: 2